Strategi Pendidikan Demokrasi di Satuan Pendidikan SMP Negeri 2 Kunjang Kabupaten Kediri - Ardhianto, Muchlas; Kartika Sari, Maya Mustika (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Democratic education has an important role in shaping students’ character. The introduction of democratic values is not enough to be done through learning activities, but it must provide direct experience for students. However, the application of democratic values in the school environment does not always run smoothly. Family cultural factors, socio-political conditions around the school, and students’ knowledge become challenges. This study aims to describe the strategies used in implementing democracy education at SMP Negeri 2 Kunjang, Kediri Regency. This research uses Fred R. David’s theory and uses a qualitative research approach with descriptive methods. The data collection techniques used are interviews, observation and documentation. The data validity test in this research is source triangulation with data analysis using the Miles and Huberman model. The results of this study show that the school has a main strategy, namely integrating learning with the Pancasila Student Profile Strengthening Project on the theme of Voice of Democracy. The second strategy is to practice democracy through the election of student council leaders. The third strategy is to build a sense of brotherhood through social family activities.